Transportation of Cull Sows—Deterioration of Clinical Condition From Departure and Until Arrival at the Slaughter Plant - Thodberg, Karen; Fogsgaard, Katrine Kop; Herskin, Mette S. (Frontiers in Veterinary Science, 2019)
Cull sows may be more vulnerable to transportation compared to other swine categories, as they are typically culled after several production cycles, and hence may be injured or weak. Until now, transportation of sows has received very little scientific attention. We aimed to investigate whether the clinical condition of the sows changed during transportation from commercial Danish farms to slaughter plants, and to initiate identification of potential risk factors for such deterioration. This observational study included 522 sows in 47 batches from 12 farms, varying according to transportation time from farm to slaughter plant. Standardized clinical examinations were conducted on-farm and on the slaughter plant. In addition, data on transportation duration, number and duration of stops, temperature during driving, and during waiting before unloading were collected. The sows' median parity was five (range 1–11) and close to 40% were lactating at the day of transportation. The mean duration of transportation was 232 ± 113 min, and the mean temperature in the trucks was 14.1 ± 5.3°C. Half of the clinical variables recorded before and after transportation changed significantly. Among these were injuries (e.g., superficial skin lesions, totally, P < 0.000; front, P < 0.001; wounds, P < 0.001; gait score, P < 0.001), and measures possibly related to heat stress (e.g. skin elasticity, P < 0.001). Three sows arrived in a condition as legally unfit for transport. The deterioration of the sows' condition was mainly related to transportation factors, such as temperature and duration—often in interaction—as well as duration of stops during the journey and while waiting before unloading. The changes in clinical condition were less dependent on the pre-transportation clinical condition of the sows, such as parity, body condition score and gait score. The results show that the clinical condition of the cull sows deteriorated from farm to slaughter plant, thereby adding data to the debate on fitness for transport of cull sows. The main risk factors were not related to characteristics of the sows, but of the journeys. Future studies should focus on identifying and distinguishing between risk factors in order to develop procedures that allow transportation of cull sows to slaughter without jeopardizing their welfare.